2020
DOI: 10.1016/j.jval.2020.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Defining Patient Engagement in Research: Results of a Systematic Review and Analysis: Report of the ISPOR Patient-Centered Special Interest Group

Abstract: Objectives: Lack of clarity on the definition of "patient engagement" has been highlighted as a barrier to fully implementing patient engagement in research. This study identified themes within existing definitions related to patient engagement and proposes a consensus definition of "patient engagement in research." Methods: A systematic review was conducted to identify definitions of patient engagement and related terms in published literature (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 173 publications
0
77
0
Order By: Relevance
“…There are many discussions relevant to defining and understanding different concepts in this area, e.g. Harrington et al [20]. We will not go further into these discussions, but instead focus on the aim of our study, which is to examine how to engage patient partners most effectively in the research process.…”
Section: Stage 1: Identification Of the Research Questionmentioning
confidence: 99%
“…There are many discussions relevant to defining and understanding different concepts in this area, e.g. Harrington et al [20]. We will not go further into these discussions, but instead focus on the aim of our study, which is to examine how to engage patient partners most effectively in the research process.…”
Section: Stage 1: Identification Of the Research Questionmentioning
confidence: 99%
“…The survey development included patient engagement exercises consistent with recommended good practice [17]. A four-step-process was followed: (1) desk-top review to identify concept elicitation studies investigating HRQoL and functioning in iTTP (January 2019; as expected, the initial search yielded limited findings, and the search was extended to all forms of TTP); (2) concept elicitation exercise with three adults with iTTP, recruited through the TTP Network; (3) concept mapping to select relevant PROMs and define bespoke questions; and (4) cognitive debriefing conducted with three UK adults living with iTTP to confirm understanding and relevance of questions.…”
Section: Survey Developmentmentioning
confidence: 99%
“…The narratives from searches of social media reinforce the observation that living with NASH can have a profound impact on many aspects of patients’ lives, including their ability to conduct day-to-day activities, their personal and social relationships, and, ultimately, their HRQoL [ 40 , 41 ]. Clinical experts and patient representatives reviewed the findings from the searches of the literature and social media and confirmed that the findings largely matched their views of the patient experience.…”
Section: Resultsmentioning
confidence: 99%
“…Development of the NASH-CHECK aligned with regulatory expectations [ 22 – 24 ] and good research practices [ 40 ]. The FDA guidance makes a number of recommendations for PROs that are to be used for label claims.…”
Section: Discussionmentioning
confidence: 99%